Studi Proses Penerimaan Diri (Self Acaptance) Pada Orang Tua Anak Tuna Grahita pada Klien "A" ” di SLB Karya Ibu Palembang - Okta Amelia; Abdur Razzaq; Lena Marianti (Social Science and Contemporary Issues Journal, 2023)
Children are the fruit of the heart, children are also the light of the eye, the pillar of hope and the pride of the family. Knowing that their child has special needs is a very surprising thing for parents to analyze this problem. Researchers use a humanistic view, which is a movement that aims to place humans in a real human position. This triggers researchers to take the title: "Self-Acceptance Process Studies." (Self Acceptance) in Parents of mentally retarded children in Client "A" in a Humanistic Perspective at SLB Karya Ibu Palembang" and this study aims to determine the factors of self-acceptance in parents of mentally retarded children in client "A" in a humanistic perspective at SLB Karya Ibu Palembang and knowing the process of self-acceptance to parents of mentally retarded children on client "A" in a humanistic perspective at SLB Karya Ibu Palembang. This research is a qualitative research with the type of field research (field research). So this research can also be called case research or case study with a qualitative descriptive approach. The condition of client "A" who has a mentally retarded child is his youngest child. He only found out about this condition when his son was in junior high school, but the symptoms of mental retardation appeared when his son was 3 years old. With this humanistic perspective, researchers see that the development of clients can accept their child's condition as a whole because humanistic is learning that must be moved from humans who are able to understand and accept themselves based on their needs. acceptance of one's own existence.